Curve Slope #1

Calculus Level 2

Find the slope of the line tangent to function f ( x ) = 3 x 2 + 6 x + 3 f(x)=3x^2+6x+3 at x = 3 x=3 without a graphing calculator.


The answer is 24.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Ethan Mandelez
Apr 7, 2021

f ( x ) = 3 x 2 + 6 x + 3 f(x) = 3x^{2} + 6x + 3

f ( x ) = 6 x + 6 f'(x) = 6x + 6

Since the derivative of a function gives us the slope of the line tangent to the function at a certain point on the graph, substituting x = 3 x=3 we get:

f ( x ) = 18 + 6 = 24 f'(x) = 18 + 6 = \boxed{24}

Just C
Apr 6, 2021

The first thing that should come to mind when thinking of finding the slope of a curve at a certain point (finding the slope of the line tangent to a point on a curve) is derivatives. Note that by deriving f ( x ) f'(x) , we can plug in x = 3 x=3 to find the slope of the line tangent to f ( x ) = 3 x 2 + 6 x + 3 f(x)=3x^2+6x+3 at x = 3 x=3 , as derivatives are a measure of the rate of instantaneous change, or the sensitivity of a function to change of its input.

Using the sum rule (if f ( x ) = g ( x ) + h ( x ) + . . . f(x)=g(x)+h(x)+... , then f ( x ) = g ( x ) + h ( x ) + . . . f'(x)=g'(x)+h'(x)+... ) and power rule (if f ( x ) = a x b f(x)=ax^b , then f ( x ) = a b x b 1 f'(x)=abx^{b\,-\,1} ), we can find the derivative of f ( x ) f(x) without needing to solve lim Δ x 0 f ( x + Δ x ) f ( x ) Δ x \displaystyle\lim_{\Delta x\to 0}{{f(x+\Delta x) - f(x)}\over{\Delta x}} for f ( x ) = 3 x 2 + 6 x + 3 f(x)=3x^2+6x+3 .

Given:

  • f ( x ) = j ( x ) + k ( x ) + l ( x ) f(x)=j(x)+k(x)+l(x)

  • j ( x ) = 3 x 2 j(x)=3x^2

  • k ( x ) = 6 x k(x)=6x

  • l ( x ) = 3 l(x)=3

Then f ( x ) = j ( x ) + k ( x ) + l ( x ) f'(x)=j'(x)+k'(x)+l'(x) .

  • j ( x ) = 3 × 2 x 2 1 = 6 x j'(x)=3\times 2x^{2\,-\,1}=6x

  • k ( x ) = 6 k'(x)=6

  • l ( x ) = 0 l'(x)=0

  • f ( x ) = j ( x ) + k ( x ) + l ( x ) = 6 x + 6 f'(x)=j'(x)+k'(x)+l'(x)=6x+6

We can then plug in x = 3 x=3 , which gives: 6 ( 3 ) + 6 = 24 6(3)+6=\boxed{24} , which must be the slope of the line tangent to f ( x ) = 3 x 2 + 6 x + 3 f(x)=3x^2+6x+3 at x = 3 x=3 .

Nice and detailed explanation! 👍

Ethan Mandelez - 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...